Formar para a sala de aula longe da sala de aula : a expansão neoliberal da educação, regulada pelo Estado, por meio das licenciaturas EAD - Mikolaiczik, Daniê Regina (2025)
The figures for undergraduate degree programs show that, currently, the majority of Brazilian teachers obtain their degrees from for-profit institutions and through distance learning. The National Education Guidelines and Bases Law (Law No. 9,394 of 1996) is crucial in defining this scenario, as it regulates, for the first time, distance learning in undergraduate programs. The general objective of this thesis, through an analysis of educational legislation, was to identify and problematize the State's responsibilities in the expansion of distance learning undergraduate programs. The aim was to examine whether or not there were markers of neoliberal rationality in the legislation that enabled the growth of distance learning in initial teacher training programs for Brazilian teachers. The research problem was defined as follows: "Since the State is the regulator of educational policies for Brazilian higher education, what interests and rationales underlie the expansion of distance learning undergraduate programs?" Methodologically, the research was characterized as basic in nature, exploratory in terms of objectives, qualitative in terms of the approach to the problem, bibliographical and documentary in terms of procedures. The basic theoretical framework was Dardot and Laval (2016), Ball (2022) and Bourdieu (2015), among others. Ten pieces of legislation dealing with distance education and undergraduate courses were selected, and the categories of privatization and flexibilization were used for the Content Analysis of the documents. The thesis was anchored in the following methodological triangulation: a literature review, a State of Knowledge review of theses on the topic, and the legislation studied. The main findings of the research indicated that the State, through complicit educational legislation, allowed—and even encouraged—the predominance of distance learning: a teaching modality, especially that offered in for-profit institutions, that reproduces inequalities compared to higher education by maintaining historical and structural distances; it promotes the erosion of academic relationships, the destruction of collective forms and democratic principles, as it prepares individuals who normalize the exchange of stability for precariousness disguised as flexibility, of solidarity for isolation; it fosters an economic, cultural, and political transformation in education, as it turns higher education into a business, bases curricula on the dictates of the market and performativity, and replaces collective interests with competitive relationships, in which the focus is on production, even if lacking depth.